Beijing 2008: Men 100m race analysis. Bolt's 9.69s. Analysis of speed during the world record. How fast did Bolt run? - Tucker, R.; Dugas, J. (2008)
According to these data, his peak speed was hit at 50m, and he then maintained this all the way to 80m, running at about 44 km/hour.